Education and Training for a Sustainable Indonesian Workforce: A Literature Review - Vaniarinanta, Irene Nadia; Susanti, Hermi; Darmastuti, Ismi (Research Horizon, 2025)
Education and training are key steps in improving the quality of human resources. Labor productivity is influenced by education and training that can develop knowledge and skills. This study examines the role of education and training in preparing and empowering Indonesia's workforce to face future challenges. The study analyses how quality education and training can equip the workforce with essential skills and knowledge to adapt to market dynamics and support sustainable development. Through a literature review method, the study shows that investment in human capital through education and training not only improves the competitiveness of the workforce in the global arena but also contributes significantly to inclusive and sustainable economic growth. The results of this study emphasize the importance of synergies between education, sustainable development strategies, and improving access to quality education and training programs for employees in Indonesia. These synergies are key to realizing a workforce that is competent, adaptive, and ready to contribute to a more just, prosperous, and environmentally friendly future for Indonesia.